Comparison of Different Resection Tools for Human Calcified Aortic Valves. Issue 4 (July 2014) - Marczynski-Bühlow, Martin; Groß, Justus; Berndt, Rouven; Röcken, Christoph; Wedel, Thilo; Böttner, Martina; Cremer, Jochen; Lutter, Georg; Petzina, Rainer
Objective: Symptomatic severe aortic valve stenosis is a disease primarily found in patients of advanced age. The standard therapy is the aortic valve replacement. Transcatheter aortic valve implantation (TAVI) is a treatment for patients ineligible for conventional aortic valve replacement. To minimize the incidence of TAVI-related complications, such as paravalvular leakage, pacemaker necessity, and ostial coronary occlusion, our research group works on the development of resection tools for aortic valves. The aim of this study was to investigate ex vivo different resection tools for human calcified aortic valves concerning cross-section morphology. Methods: With the use of 12 human calcified aortic leaflets, the effect of laser scalpel, punching device, and scissors on cross-section morphology was investigated. Scanning electron microscopy and histological analyses were applied to evaluate the cutting surface area. Results: The cross-section areas created by a laser scalpel were smooth, regular, and uniform, whereas these areas were rough, irregular, and inhomogeneous when using the scissors or the punching device. Quantitative analysis of the cutting edges demonstrated significant differences between the three resection tools. The best results were obtained for the laser scalpel compared with the punching device ( P < 0.001) and for the laser scalpel compared with the scissors ( P < 0.05), whereas the scissors compared with the punching device showed no significant differences ( P > 0.05). Conclusions: Laser cutting of human calcified aortic valves demonstrated the best results concerning homogeneous cross-section morphology compared with the punching device and the scissors and seems to be a promising tool for aortic valve resection during TAVI procedures in the future.